2021
DOI: 10.2478/mjhr-2021-0003
|View full text |Cite
|
Sign up to set email alerts
|

Seed Priming Significantly Affects Germination and Post Germination Early Seedling Growth in Okra

Abstract: Seed priming significantly affects germination and post germination emergence in seedling of plants. Okra is an important vegetable plays significant role in human nutrition. However, little information is available regarding effect of seed priming on germination and post germination early vegetative growth. Therefore, a pot experiment was conducted to find out the effect of seed priming on the emergence and seedling vigor in different okra varieties. Six local Bangladeshi okra varieties were primed in water f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The GP of Hisar Unnat okra is 66.3% [ 39 ]. Under seed priming conditions, the GPs of six okra accessions were 25.33–88.00% [ 40 ]. In this study, the 180 okra accessions had a GP of 80.41% on day 7 under the CK condition, while the GP on day 3 was only 70.81%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The GP of Hisar Unnat okra is 66.3% [ 39 ]. Under seed priming conditions, the GPs of six okra accessions were 25.33–88.00% [ 40 ]. In this study, the 180 okra accessions had a GP of 80.41% on day 7 under the CK condition, while the GP on day 3 was only 70.81%.…”
Section: Discussionmentioning
confidence: 99%
“…Further statistical analysis of these SNPs revealed that 167 were detected by both programs simultaneously, and they are relatively stable SNP loci (Table S5). These 167 SNPs were located on 21 of the 65 okra chromosomes, namely, chromosomes 4,5,15,17,19,22,24,25,31,37,40,41,43,44,45,46,54,56,59, 61, and 64. Among them, chromosome 31 had the most marker-trait associations (66) detected.…”
Section: Gwas Of Gp Under Ck and Salt Stress Conditionsmentioning
confidence: 99%
“…Seed germination is the process by which a dormant seed becomes a healthy seedling (Chen et al, 2021). The process of radicle formation involves several steps, including water absorption, molecular breakdown, genetic material repair, endosperm and embryo elongation, and seed coat disintegration (Rima, 2021;Rhaman et al, 2020). Successful germination is crucial for both the final product and the early-stage development of seedlings (Khanal et al, 2022;Kharat and Pottathil, 2021).…”
Section: Introductionmentioning
confidence: 99%